Infant-led Research: Privileging Space to See, Hear, and Consider the Subjective Experience of the Infant - Bunston, Wendy; Frederico, Margarita; Whiteside, Mary (Australian social work, 2020)
The subjective experience of infants is seldom considered in research directly concerning them. Commonly, infants are not believed to possess self-agency or innate communicative abilities, obscuring space for researchers to consider the infant's subjectivity. Rather, measuring and coding behaviour or seeking the parent's perspective is privileged. Making meaning is not limited to the capacity to verbalise; as meaning encompasses feelings, behaviours, and contexts. In this paper, a novel "infant-led" qualitative research methodology is presented utilising infant observation techniques, drawing on theories of "intersubjectivity" and using a constructivist grounded theory method. Distinct to this methodology is how data collection begins with the infant before any other, as does the process of data analysis; providing the basis upon which all other data are interpreted. The application of such an approach is nonintrusive and has much to offer social workers working with infants in high risk situations in community, health, and mental health settings. IMPLICATIONS The experience of infants is entitled to be included in research that directly impacts them. Adopting an infant-led approach brings alive the experiences of infants and challenges assumptions that minimise the competencies and contributions infants make.